Analisis Psikospiritual Fenomena Relapse Bagi Kelompok ODGPZ di Loka Rehabilitasi BNN Deli Serdang Tahun 2024 - Via Epiphanis Halawa; Reymond Pandapotan Sianturi; Grecetinovitria Butar-Butar (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Relapse is a relapse behavior that repeatedly occurs after undergoing rehabilitation characterized by the emergence of addictive mindsets, behaviors and actions after the withdrawal period. Drug cases create a sense of dependence caused by several factors, namely family factors, social factors, employment factors, psychological factors and spiritual factors. That's why the case causes uncontrolled emotions of wanting to collect. The focus of the research is to analyze in depth the psychospiritual of ODGPZ who experience continuous relapse in the Rehabilitation Workshop. The term psychospiritual refers to psychology and spirituality where the psychological dimension affects the spiritual experience and the spiritual dimension can affect psychology. Spirituality and psychology include the search for identity which raises various questions that can cause problems in oneself that make oneself anxious, depressed, unstable mood and feeling like they have no purpose in life. Psychospirituality is used as a tool or analytical knife for counselors to dismantle spiritual problems experienced by counselors and see patterns of relapsed behavior. The purpose of the study was to determine the pattern of relapse behavior for the ODGPZ group and analyze the pattern of relapse behavior using a psychospiritual perspective at the BNN Deli Serdang Rehabilitation Workshop. This study uses a qualitative research methodology with a case study method to clients who have experienced relapse. Data collection techniques were obtained by initial observation, interviews and documentation. The results of the analysis showed that the pattern of relapse behavior by ODGPZ was extraordinary enjoyment, suggestions from ODGPZ friends, increasing the spirit of activity, escaping from problems, and pressure and stigma from society. After the pattern was analyzed using a psychospiritual lens, the author found that there were clients who still found it difficult to refuse offers from ODGPZ friends, there were errors in interpreting the theological message of the Bible text, all problems were solved with drugs, finding meaning and purpose in life and social change. Therefore, psychospirituality is closely related to the intellectual and emotional of the individual which affects the mindset and behavior of individuals, especially drug user.